Low-Cost Monitoring and Control for Melon Cultivation in Greenhouse using Internet of Thing and Drip Irrigation - Supriyanto; Rafli Arya Fahrezi; Tegar Adi Prasetyo; Ananda Putra Septiadi; Lilis Sucahyo; Mohamad Solahudin (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2025)
Melons are become a popular fruit cultivating inside the greenhouse using the drip irrigations in Indonesia. The application of internet of things-based monitoring is beneficial to optimize cultivation management. Another issue on melon cultivation inside the greenhouse is automation of the water and nutrient delivery. However, currently monitoring and control is expensive and difficult to modify by farmers. The aim of this study was to develop a low-cost technology and easy to use by farmers using internet of technology. The method used in this study consisted of analysis, design and implementation. The result of this study was a system monitoring to monitor air temperature, air humidity, media humidity and solar radiation inside the greenhouse integrated with nutrient or water delivery using drip irrigation. A web-based dashboard was developed as a user interface for the farmers and users. The overall cost to develop a system monitoring and control was 358.24 USD not including the water thank and nutrient delivery system (pump and irrigations pipe). The system was deployed and tested at Agribusiness and technology park IPB University.